Characterization of Mucosa-Associated Microbiota in Matched Cancer and Non-neoplastic Mucosa From Patients With Colorectal Cancer - Leung, Polly H. M.; Subramanya, Rao; Mou, Qianqian; Lee, Katherine Ting-wei; Islam, Farhadul; Gopalan, Vinod; Lu, Cu-tai; Lam, Alfred King-yin (Frontiers in Microbiology, 2019)
Colonic microbiota play important roles in the development of colorectal cancer. We aim to characterise the mucosa-associated microbiota in the tumour as well as the matched non-neoplastic mucosa from patients with colorectal cancer. Microbiota profiling in these samples was done using high-throughput 16S rRNA amplicon sequencing. Our results showed that the microbiota richness and diversity were similar between the tumour and non-neoplastic mucosae. Linear discriminant analysis effect size (LEfSe) analysis identified Fusobacterium and Campylobacter as the key genera of the tumour while Brevundimonas as the key genus of the non-neoplastic mucosa. In patients with shorter survival period, the relative abundance of Fusobacterium and Campylobacter was significantly higher in the tumour. Besides, regardless of the sites, tumour showed higher abundance of Fusobacterium. On the other hand, the relative abundance of Brevundimonas was significantly lower in the tumour. When validated with quantitative ddPCR, we found the absolute numbers of both Fusobacterium and F. nucleatum were significantly higher in the carcinoma from patients with shorter survival period, conventional type of adenocarcinoma in the distal portion of the large intestine (descending colon, sigmoidal colon, and rectum). In conclusion, our study showed a compositional alteration in the mucosa-associated microbiota in the tumour, which may contribute to the progression of colorectal cancer.